An Exploration On Project Assessment Of Students’ Oral Productive Skills: A Study Of Access Microscholarship Students - Nurdin Noni; Baso Jabu; Samtidar Samtidar (Seminar Nasional LP2M UNM, 2017)
This research aims at finding out how the teacher manages the project assessment and what the students’ perception towards the project work as a part of project assessment. Descriptive qualitative research design is applied to explore the two objectives. In terms of subject, the researchers focus on observing class B of the English Access Microscholarship students, provided by Bureau of Educational and Cultural Affairs of USA at UNM. They are chosen purposively among 3 classes in total. The researchers take one class as the subject, which consists of 20 students. The other subject is the English teacher of this class. The researchers attended the class to do direct observation and interviewed 20 students. In doing the observation, the researchers used observation checklist to identify the activities in classroom interaction. Interview was conducted by using audio recorder to obtain data concerning the students’ perception toward the project work. The result of the study reveals the way teacher assessed the project assessment, assessing four aspects namely planning, collecting data, processing data and report. Teacher broke them down in managing the assessment. In this study, the teacher managed the assessment by dividing those aspects into some parts. Planning consisted of preparation and title, and collecting data covered information gathering. Following this, processing data consists of writing, analyzing data and concluding. Finally, project report consists of presenting, retelling, telling experience and performing. Regarding students’ perceptio n, students perceived that project work in project assessment is helping, interesting, motivating, exciting and different from other forms of assessment. Key words: Project Assessment, Oral Productive Skills